Respuesta :
Answer:
c) [tex]6^6[/tex]
Step-by-step explanation:
[tex]\dfrac{12^6}{2^6}[/tex]
factor [tex]12^6 =(3 \cdot 4)^6= (3 \cdot 2^2)^6=3^6 \cdot 2^{12}[/tex]
[tex]\implies \dfrac{12^6}{2^6}=\dfrac{3^6 \cdot 2^{12}}{2^6}[/tex]
Apply exponent rule [tex]\frac{a^b}{a^c} =a^{b-c}[/tex]:
[tex]\implies \dfrac{3^6 \cdot 2^{12}}{2^6}=3^6 \cdot 2^6[/tex]
Apply exponent rule [tex](a^b \cdot c^b)=(ac)^b[/tex]:
[tex]\implies 3^6 \cdot 2^6=(3 \cdot 2)^6=6^6[/tex]
Hey there!
12^6 / 2^6
12^6
= 12 * 12 * 12 * 12 * 12 * 12
= 144 * 144 * 144
= 20,736 * 144
= 2,985,984
= 2,985,984/2^6
2^6
= 2 * 2 * 2 * 2 * 2 * 2
= 4 * 4 * 4
= 16 * 4
= 64
= 2,985,984/64
= 2,985,984 ÷ 64 / 64 ÷ 64
= 46,656 / 1
= 46,656 ÷ 1
= 46,656
LOOKING FOR SOMETHING THATS EQUIVALENT TO: 46,656
PROCESS OF ELIMINATION
6^0
= 6 * 1
= 6
it’s NOT
1/6^6
= 1 / 6 * 6 * 6 * 6 * 6 * 6
= 1 / 36 * 36 * 36
= 1 / 1,296 * 36
= 1 / 46,656
It’s NOT option B
6^6
= 6 * 6 * 6 * 6 * 6 * 6
= 36 * 36 * 36
= 1,296 * 36
= 46,656
Option C IS possibly your answer
6
= 6
Its NOT option D
Therefore, your answer is:
Option C. 6^6
Good luck on your assignment and enjoy your day!
~Amphitrite1040:)